The COVID-19/Tuberculosis Syndemic and Potential Antibody Therapy for TB Based on the Lessons Learnt From the Pandemic - Dass, Sylvia Annabel; Balakrishnan, Venugopal; Arifin, Norsyahida; Lim, Crystale Siew Ying; Nordin, Fazlina; Tye, Gee Jun (Frontiers in Immunology, 2022)
2020 will be marked in history for the dreadful implications of the COVID-19 pandemic that shook the world globally. The pandemic has reshaped the normality of life and affected mankind in the aspects of mental and physical health, financial, economy, growth, and development. The focus shift to COVID-19 has indirectly impacted an existing air-borne disease, Tuberculosis. In addition to the decrease in TB diagnosis, the emergence of the TB/COVID-19 syndemic and its serious implications (possible reactivation of latent TB post-COVID-19, aggravation of an existing active TB condition, or escalation of the severity of a COVID-19 during TB-COVID-19 coinfection), serve as primary reasons to equally prioritize TB. On a different note, the valuable lessons learnt for the COVID-19 pandemic provide useful knowledge for enhancing TB diagnostics and therapeutics. In this review, the crucial need to focus on TB amid the COVID-19 pandemic has been discussed. Besides, a general comparison between COVID-19 and TB in the aspects of pathogenesis, diagnostics, symptoms, and treatment options with importance given to antibody therapy were presented. Lastly, the lessons learnt from the COVID-19 pandemic and how it is applicable to enhance the antibody-based immunotherapy for TB have been presented.